2022
DOI: 10.3390/biomedicines10081798
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pharmacogenetics to Optimize Immunosuppressant Therapy in Kidney-Transplanted Patients

Abstract: Immunosuppressant drugs (ISDs) are routinely used in clinical practice to maintain organ transplant survival. However, these drugs are characterized by a restricted therapeutic index, a high inter- and intra-individual pharmacokinetic variability, and a series of severe adverse effects. In particular, genetic factors have been estimated to play a role in this variability because of polymorphisms regarding genes encoding for enzymes and transporters involved in the ISDs pharmacokinetic. Several studies showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 91 publications
0
11
0
1
Order By: Relevance
“…In order to optimize the immunosuppressant therapy in kidney-transplanted patients, pharmacogenetics studies have been considered. In this respect, Urzì Brancati et al proposed that the characterization of the polymorphisms in CYP3A5, CYP3A4, ABCB1, and UGT1A9 genes could be a strategy to select the ideal dosage for each patient [ 61 ].…”
Section: Rapamycin In Organ and Tissue Transplantationmentioning
confidence: 99%
“…In order to optimize the immunosuppressant therapy in kidney-transplanted patients, pharmacogenetics studies have been considered. In this respect, Urzì Brancati et al proposed that the characterization of the polymorphisms in CYP3A5, CYP3A4, ABCB1, and UGT1A9 genes could be a strategy to select the ideal dosage for each patient [ 61 ].…”
Section: Rapamycin In Organ and Tissue Transplantationmentioning
confidence: 99%
“…Here, we found that daily administration of 10 mg/Kg/day Tac (Tac-10) for 10 days was associated with high blood pressure, an increase in plasma creatinine, and renal damage, represented by the induction in IL-6 and NGAL, two mediators linked to the proinflammatory status [ 45 , 46 , 47 , 48 ]. The dose of Tac used was several times higher than the dose administered to transplant patients [ 49 , 50 ]. However, a study found that C57BL/6 mice might show differences in the resistance to nephrotoxicity induced by drug models (for example, cisplatin) [ 51 ] or to other acute kidney injury (AKI) experimental models driving to chronic kidney disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the methodology described by Urzi Brancati et al [ 10 ], we considered all articles, written in English, where an analysis was made of the role of genetics in IS drug bioavailability and metabolization. We excluded redundant articles and when results showed also another kind of transplantation we privileged articles dealing with kidney transplantation.…”
Section: Methodsmentioning
confidence: 99%